The kinematic correction to a reaction of quasielastic electron scattering by intranuclear nucleons - Dementiy, S.V. (Вопросы атомной науки и техники, 2000)
The problem of compatibility and interpretation of the data on quasi-elastic electron scattering on nuclei in a reaсtion A(е,е'р), obtained in essentially various kinematic conditions is considered. It is shown that in such cases it is necessary to introduce the kinematic correction into the intranuclear nucleon momentum defined by the laws of energy and momentum conservation. The correction value can be defined as a first approximation from the inclusive A(е,е') reaction. The reasoning are illustrated by an example of a reaction 4Не(е,е'р)Т.